An Analysis of the Use of Puzzle-Based Learning Media in Enhancing Students' Interest in Science Subjects in Grade V at SD Negeri 19 Tulang Bawang Udik - Asri Nuraini; Mahmudah, Masrurotul; Nurul Aisyah (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
Puzzle learning media is widely applied at elementary school level because it is useful in focusing students' attention and motivating. This media not only functions as a tool to increase students' concentration, but is also an effective way to increase interest in learning. By using interesting and interactive learning media, such as puzzles, students can learn in a fun way while increasing their understanding of the material being taught. The aim of this research is to find out how the use of puzzle learning media can increase students' interest in learning in science subjects in Class V of SD Negeri 19 Tulang Bawang Udik. This research uses a qualitative approach with descriptive methods. The data collection techniques used were interviews, observation and documentation. The subjects of this research were teachers and students of class V at SD Negeri 19 Tulang Bawang Udik.  This research data was analyzed by data reduction, data presentation, and drawing conclusions or verification. The results of this research show that the use of puzzle learning media can increase students' interest in learning. This is characterized by an increased sense of enjoyment in the learning process, active involvement of students, students' interest in the material and participating in learning well, showing students' attention to the learning process, showing students' attention, such as listening to the teacher's explanation.